Legal Status of Mercy Killing in Islamic Law - Niazi, Mustafa (الدراسات الإسلامية, 2020)
This paper investigates the legal status of mercy killing in Islam. Human body and soul are considered sacred in Islamic law. Therefore, Islam ordains various principles and legal rules for the protection of human life and body. For this reason, homicide without a legal justification is a capital offence. However, the idea of mercy killing (i.e., euthanasia) has gained prominence as a means to end the life of a person who suffers from some incurable disease. Mercy killing either be active such as introducing effective way to facilitate the termination of the patient’s life, or passive such as discontinuing his medical treatment. This paper studies and analyzes different views and approaches of the scholars of Islamic law with respect to this modern phenomenon. Keywords Mercy Killing, Euthanasia, Medical Treatment, Islamic Law, Incurable Disease.